2024
DOI: 10.1021/acsptsci.4c00223
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted (N)-Methanocarba A3 Adenosine Receptor Agonists: In Silico, In Vitro, and In Vivo Characterization

Dilip K. Tosh,
Matteo Pavan,
Chunxia Cronin
et al.

Abstract: 2-Arylethynyl (N)-methanocarba adenosine 5′methylamides are selective A 3 adenosine receptor (AR) agonists containing a preestablished receptor-preferred pseudoribose conformation. Here, we compare analogues having bulky 2substitution, either containing or lacking an ethynyl spacer between adenine and a cyclic group. 2-Aryl compounds 9−11, 13, 14, 19, 22, 23, 27, 29, 31, and 34, lacking a spacer, had human (h) A 3 AR K i values of 2−30 nM, and others displayed lower affinity. Mouse (m) A 3 AR affinity varied,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…We used the same de novo model we recently introduced, which contains a bound adenosine as an agonist and the α subunit of the G i protein . This model was compared to the recently released hA 3 AR structures (coordinates released while this manuscript was under review), and the structure and our model were shown to have an RMSD of ∼1.4 Å, which is lower than the structural resolution . Since 3 and 27 are structurally similar, we performed template-docking with the Glide-SP protocol, starting from the validated pose of 3 to obtain a putative 27 binding conformation within the allosteric pocket.…”
Section: Resultsmentioning
confidence: 99%
“…We used the same de novo model we recently introduced, which contains a bound adenosine as an agonist and the α subunit of the G i protein . This model was compared to the recently released hA 3 AR structures (coordinates released while this manuscript was under review), and the structure and our model were shown to have an RMSD of ∼1.4 Å, which is lower than the structural resolution . Since 3 and 27 are structurally similar, we performed template-docking with the Glide-SP protocol, starting from the validated pose of 3 to obtain a putative 27 binding conformation within the allosteric pocket.…”
Section: Resultsmentioning
confidence: 99%